The interpretation of forensic DNA profiles: an historical perspective. Issue 2 (2nd April 2020) - Bright, Jo-Anne; Kelly, Hannah; Kerr, Zane; McGovern, Catherine; Taylor, Duncan; Buckleton, John S.
ABSTRACT: The advent of DNA profiling in the 1980s has revolutionised forensic science. Forensic DNA profiling is a powerful tool that is used to both exonerate and implicate persons of interest in criminal cases. The technologies used to recover and detect DNA from crime scene stains have evolved over time. Whereas 30 years ago most forensic profiles were generated from visible stains such as blood or semen, nowadays, DNA profiles are often generated from trace amounts of DNA including touched items. The DNA in these profiles is often compromised in quantity and quality, and frequently originates from more than one individual. This improved sensitivity has complicated the interpretation of forensic DNA profiles, and consequently improved methods of profile interpretation have had to be developed. The adoption of these methods has meant that forensic scientists can now interpret mixed DNA profiles previously thought to be too complicated. This article reviews the history of forensic DNA profiling globally, introduces the challenges of DNA profile interpretation, discusses why the community is adopting improved methods, and reflects on what new technology is on the horizon and the new challenges that may present.